Hepatitis C virus core antigen testing in liver and kidney transplant recipients. Issue 11 (19th November 2013) - Heidrich, B.; Pischke, S.; Helfritz, F. A.; Mederacke, I.; Kirschner, J.; Schneider, J.; Raupach, R.; Jäckel, E.; Barg‐Hock, H.; Lehner, F.; Klempnauer, J.; von Hahn, T.; et al.
Summary HCV RNA levels correlate with the long‐term outcome of hepatitis C in liver transplant recipients. Nucleic acid testing (NAT) is usually used to confirm HCV reinfection and to examine viral loads after liver transplantation. HCV core antigen (HCVcoreAg) testing could be an alternative to NAT with some potential advantages including very low intra‐ and interassay variabilities and lower costs. The performance of HCVcoreAg testing in organ transplant recipients is unknown. We prospectively studied 1011 sera for HCV RNA and HCVcoreAg in a routine real‐world setting including 222 samples obtained from patients after liver or kidney transplantation. HCV RNA and HCVcoreAg test results showed a consistency of 98% with a very good correlation in transplanted patients (r > 0.85). The correlation between HCV RNA and HCVcoreAg was higher in sera with high viral loads and in samples from patients with low biochemical disease. Patients treated with tacrolimus showed a better correlation between both parameters than individuals receiving cyclosporine A. HCV RNA/HCVcoreAg ratios did not differ between transplanted and nontransplanted patients, and HCV RNA and HCVcoreAg kinetics were almost identical during the first days after liver transplantation. HCVcoreAg testing can be used to monitor HCV viral loads in patients after organ transplantation. However, the assay is not recommended to monitor antiviral therapies.